Exploring the Underlying Message of Kalbe Farma’s Corporate Social Responsibility (CSR) Strategy: Video Water Supply for Watuagung - Mirana Hanathasia; M. Kresna Noer; Annisa Fitriana Lestari (Journal of Social Entrepreneurship Theory and Practice, 2024)
Watuagung is an area in Indonesia that is experiencing water shortage. The lack of water caused some conflicts in the village. People fought to get clean water. In 2013, a local hero strived for water supply for the village. Moreover, now, water is easy to find in Watuagung village. Therefore, the quality of life of the people is getting better. Because of the water supply, people can harvest plants and earn money. This village achievement occurred with the involvement of Kalbe Farma, Indonesia’s pharmaceutical company, in its CSR program. Furthermore, this CSR journey is described in the short video "Akses Air untuk Watuagung." The purpose of this study is to explore the underlying message of Kalbe Farma’s CSR strategy: A case study of the video "Akses Air untuk Watuagung" from college students’ perceptions. Focus Group Discussion (FGD) conducted to explore the audience’s perceptions of the video. Five students will watch the movie at one time, and questions will be delivered among the participants of the FGD to dig into the audience’s perception. The results revealed five dominant factors in communication CSR: CSR informativeness, personal relevance, self-efficacy, self-promotional message tone, and consistency. Moreover, two factors need to be improved: third-party endorsement and transparency. This research also highlights new factors, such as CSR authenticity, stakeholder involvement, and culture.